Switchable Synthesis of 3‑Substituted 1H‑Indazoles and 3,3-Disubstituted 3H‑Indazole-3-phosphonates Tuned by Phosphoryl Groups - Chen, Guihua; Hu, Minglin; Peng, Yungui (Journal of organic chemistry, 2018)
3-Alkyl/aryl-1H-indazoles and 3-alkyl/aryl-3H-indazole-3-phosphonates were synthesized efficiently through a 1,3-dipolar cycloaddition reaction between α-substituted α-diazomethylphosphonates and arynes under simple reaction conditions. The product distribution was controlled by the phosphoryl group, which acted both as a tuning group and a traceless group in the reaction.